Environmental, Social, and Governance (ESG) Risk towards Stock Market Reaction in Indonesia - Simamora, Alex Johanes (The International Journal of Financial Systems, 2025)
Investors want to ensure that their investments will be sustainable by investing in a business that considers ESG aspects. This research aims to examine the effect of ESG risk on stock market reaction in Indonesia. Research samples include 300 observations that listed on the index of Indonesian Stock Exchange ESG Leaders. ESG risk is measured by ESG risk score. Stock market reaction is measured by abnormal return. Hypothesis test uses fixed-effect regression analysis. Based on data analysis, ESG risk has an effect on stock market reaction. The effect of ESG risk on stock market reaction occurs more in lower information asymmetry. It indicates that lower ESG risk captures effective ESG implementation and lower companies’ risks and attracts investors to buy the stock. This research provides new evidence of ESG risk on investors’ reactions on the Indonesian Stock Exchange.